Evaluating the competence of the primary vector, Culex tritaeniorhynchus, and the invasive mosquito species, Aedes japonicus japonicus, in transmitting three Japanese encephalitis virus genotypes - Faizah, Astri Nur; Kobayashi, Daisuke; Amoa-Bosompem, Michael; Higa, Yukiko; Tsuda, Yoshio; Itokawa, Kentaro; Miura, Kozue; Hirayama, Kazuhiro; Sawabe, Kyoko; Isawa, Haruhiko (PLoS neglected tropical diseases, 2020)
Japanese encephalitis virus (JEV) is maintained in an enzootic cycle between swine, water birds, and mosquitoes. JEV has circulated indigenously in Asia, with Culex tritaeniorhynchus as the primary vector. In some areas where the primary vector is scarce or absent, sporadic cases of Japanese encephalitis have been reported, with Aedes japonicus japonicus presumed to have the potential as a secondary vector. As one of the world’s most invasive culicid species, Ae . j . japonicus carries a considerable health risk for spreading diseases to wider areas, including Europe and North America. Thus, evaluation of its competency as a JEV vector, particularly in a native population, will be essential in preventing potential disease spread. In this study, the two mosquito species’ vector competence in transmitting three JEV genotypes (I, III, and V) was assessed, with Cx . tritaeniorhynchus serving as a point of reference. The mosquitoes were virus-fed and the infection rate (IR), dissemination rate (DR), and transmission rate (TR) evaluated individually by either RT-qPCR or focus forming assay. Results showed striking differences between the two species, with IR of 95% (261/274) and 9% (16/177) in Cx . tritaeniorhynchus and Ae . j . japonicus , respectively. Both mosquitoes were susceptible to all three JEV genotypes with significant differences in IR and mean viral titer. Results confirm the primary vector’s competence, but the fact that JEV was able to establish in Ae . j . japonicus is of public health significance, and with 2%–16% transmission rate it has the potential to successfully transmit JEV to the next host. This may explain the human cases and infrequent detection in primary vector-free areas. Importantly, Ae . j . japonicus could be a relevant vector spreading the disease into new areas, indicating the need for security measures in areas where the mosquito is distributed or where it may be introduced.